Australian children’s foot, ankle and leg problems in primary care: a secondary analysis of the Bettering the Evaluation and Care of Health (BEACH) data - Hylton B Menz; Christopher Harrison; Peter A Lazzarini; Cylie M Williams; Julie Gordon (BMJ Open)
Objectives To explore children’s foot, ankle and leg consultation patterns and management practices in Australian primary care.Design Cross-sectional, retrospective study.Setting Australia Bettering the Evaluation and Care of Health program dataset.Participants Data were extracted for general practitioners (GPs) and patients <18 years from April 2000 to March 2016 inclusive.Main outcome measures Demographic characteristics: sex, GP age groups (ie, <45, 45–54, 55+ years), GP country of training, patient age grouping (0–4, 5–9, 10–14, 15–18 years), postcode, concession card status, indigenous status, up to three patient encounter reasons, up to four encounter problems/diagnoses and the clinical management actioned by the GP.Results Children’s foot, ankle or leg problems were managed at a rate of 2.05 (95% CI 1.99 to 2.11) per 100 encounters during 229 137 GP encounters with children. There was a significant increase in the rate of foot, ankle and leg problems managed per 100 children in the population, from 6.1 (95% CI 5.3 to 6.8) in 2005–2006 to 9.0 (95% CI 7.9 to 10.1) in 2015–2016. Management of children’s foot, ankle and leg problems were independently associated with male patients (30% more than female), older children (15–18 years were 7.1 times more than <1 years), male GPs (13% more) and younger GPs (<45 years of age 13% more than 55+). The top four most frequently managed problems were injuries (755.9 per 100 000 encounters), infections (458.2), dermatological conditions (299.4) and unspecified pain (176.3). The most frequently managed problems differed according to age grouping.Conclusions Children commonly present to GPs for foot, ankle and leg problems. Presentation frequencies varied according to age. Unexpectedly, conditions presenting commonly in adults, but rarely in children, were also frequently recorded. This data highlights the importance of initiatives supporting contemporary primary care knowledge of diagnoses and management of paediatric lower limb problems to minimise childhood burden of disease.